Influence of Prey Size on the Predatory Behavior of Ectatomma brunneum (Hymenoptera: Formicidae) Under Laboratory Conditions - Albino, Erica [UNESP]; Tofolo, Viviane Cristina [UNESP]; Nomura, Erico [UNESP] (California State University, 2008)
The influence of prey size on the predatory behavior and behavioral sequence of Ectatomma brunneum under laboratory conditions was evaluated. Two behaviors were characterized: rejection and attack, the latter divided into individual and group attack. In the group attack, prey transport (Tenebrio molitor larvae) into the nest prevailed, whether immobilized as a consequence of the ant venom or not. on the other hand, in the individual attacks such behavior was not observed. There was no significant relation between the predatory behavior and the size of the larvae offered, indicating that prey dimensions do not interfere with predation. The high rejection rates registered in the experimental trials may have been a consequence of the absence of immatures in the nests used in the research and/or the decrease in the activities observed, considering that the experiments were carried out in the coldest time of the year.